2021
DOI: 10.1007/s40620-021-01076-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of a first dose of mRNA- or vector-based SARS-CoV-2 vaccination in dialysis patients: a multicenter prospective observational pilot study

Abstract: Background Dialysis patients are at risk for lower SARS-CoV-2-vaccine immunogenicity than the normal population. We assessed immunogenicity to a first mRNA- or vector-based SARS-CoV-2-vaccination dose in dialysis patients. Methods In a multicenter observational pilot study, 2 weeks after a first vaccination (BNT162b2/Pfizer-BioNTech [Comirnaty] or ChAdOx1 nCoV-19/Oxford-Astra-Zeneca [Vaxzevria]), hemodialysis patients (N = 23), peritoneal dialysis patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 10 publications
(8 reference statements)
8
37
1
1
Order By: Relevance
“…Prospective studies with other vaccines against COVID-19, e.g., viral vectorbased vaccines, will help to elucidate the efficacy of different vaccines in these patients. Moreover, antibody titer persistence in patients on dialysis might differ from otherwise healthy persons, which should be addressed in longitudinal observations (25).…”
Section: Discussionmentioning
confidence: 99%
“…Prospective studies with other vaccines against COVID-19, e.g., viral vectorbased vaccines, will help to elucidate the efficacy of different vaccines in these patients. Moreover, antibody titer persistence in patients on dialysis might differ from otherwise healthy persons, which should be addressed in longitudinal observations (25).…”
Section: Discussionmentioning
confidence: 99%
“…Six preprint articles were selected from the medRxiv server and another 5 studies from enrolled studies only reported the immunogenicity rates of patients receiving dialysis who did not complete the vaccination protocol (ie, those who received only 1 dose of the BNT162b, AZD1222, or mRNA-1273 vaccines). 7,[11][12][13]37 Other articles reported an antibody response rate after the second dose with or without reporting the response rate after the first dose. Three studies discussed immunogenicity rates after the booster shot.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…However, most previous studies have compared the effectiveness of vaccines according to the humoral response to SARS-CoV-2, and therefore, studies focusing on the cellular immune response following COVID-19 vaccination are warranted. On the other hand, most studies have shown the effectiveness of BNT162b2, although one study reported no significant difference in antibody response compared to AZD1222 [ 45 ]. More studies exploring the effectiveness of inactivated whole virus vaccines, viral vector vaccines, other mRNA vaccines, protein subunit vaccines, and mixed prime-boost schedules are also required.…”
Section: Effectiveness Of Covid-19 Vaccines In Hemodialysis Patientsmentioning
confidence: 99%